2019
DOI: 10.2134/age2019.07.0057
|View full text |Cite
|
Sign up to set email alerts
|

Planting Rate and Nitrogen Fertility Affect Runoff Losses during Hybrid Bermudagrass Establishment

Abstract: The high sprig planting rate resulted in faster bermudagrass establishment.• The high and low N fertilizer rates resulted in similar bermudagrass establishment.• Runoff, sediment, and nutrient losses decreased over time as groundcover increased.• High sprigging and low N fertilization rates reduce nutrient losses during establishment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…reported fertilizing with 0.25 or 1.0 lb N 1,000 ft −2 wk −1 had similar bermudagrass establishment rates from sprigging; however, the lower N rates had reduced inorganic N loss. Moderate N rates (e.g., 2.0 to 3.0 lb N 1,000 ft −2 total), however, could improve bermudagrass stolon density, reduce surface runoff, and improve water infiltration compared with non‐fertilized turf during establishment (Burwell et al., 2011; Gross et al., 1990; Rice et al., 2019). Further, controlled release fertilizers potentially reduce overall nitrate leaching and ammonia volatilization and improves N use efficiency compared with soluble N sources (Braun & Bremer, 2018; Shoji et al., 2007; Wilson et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported fertilizing with 0.25 or 1.0 lb N 1,000 ft −2 wk −1 had similar bermudagrass establishment rates from sprigging; however, the lower N rates had reduced inorganic N loss. Moderate N rates (e.g., 2.0 to 3.0 lb N 1,000 ft −2 total), however, could improve bermudagrass stolon density, reduce surface runoff, and improve water infiltration compared with non‐fertilized turf during establishment (Burwell et al., 2011; Gross et al., 1990; Rice et al., 2019). Further, controlled release fertilizers potentially reduce overall nitrate leaching and ammonia volatilization and improves N use efficiency compared with soluble N sources (Braun & Bremer, 2018; Shoji et al., 2007; Wilson et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Rice et al reported fertilizing with 0.25 or 1.0 lb N 1,000 ft −2 wk −1 had similar bermudagrass establishment rates from sprigging; however, the lower N rates had reduced inorganic N loss. Moderate N rates (e.g., 2.0 to 3.0 lb N 1,000 ft −2 total), however, could improve bermudagrass stolon density, reduce surface runoff, and improve water infiltration compared with non-fertilized turf during establishment (Burwell et al, 2011;Gross et al, 1990;Rice et al, 2019). Further, controlled release fertilizers potentially reduce overall nitrate leaching and ammonia volatilization and improves N use efficiency compared with soluble N sources F I G U R E 3 Relationship between average dry matter yield (DMY) 47 and 54 days after planting and days to 90% green coverage for eight grow-in fertility programs as calculated using an exponential decay model (A), and the relationship of total nitrogen (N) applied for eight fertility programs and average dry matter yield (DMY) calculated using simple linear regression using Graphpad Prism (B).…”
Section: Discussionmentioning
confidence: 99%
“…Fertilization affects color, growth, yield and green up of warm season grasses, as bermudagrass (Serena et al, 2018). Bermudagrass is grown on athletic fields, because of its quality, excellent wear tolerance, and vigorous growth (Rice et al, 2019). Fertilization is an essential management practice to maintain the health and performance of greens (Throssell et al, 2017), where, e.g., a hybrid of bermudagrass with high nutritional requirements is used, and where daily mowing are made at certain times of the year, with the clippings removed from the site, an outflow of nutrients from the system.…”
Section: Introductionmentioning
confidence: 99%
“…Versatility and affordability of establishment-whether from seed, sprigs, or sod-make common bermudagrass [Cynodon dactylon (L.) Pers.] a popular choice for home lawns and low-input areas (Chalmers et al, 2006;Rice et al, 2019;Taliaferro et al, 2004). Significant soil disturbance may occur before turfgrass establishment, often resulting in the removal of topsoil.…”
mentioning
confidence: 99%